Gimme' the Loop: Modifications to the Squid-Capture Technique for Laser-Fenestrated Thoracic Endografting. (August 2021) - Mulorz, Joscha; Knapsis, Artis; Ertas, Neslihan; Schelzig, Hubert; Wagenhäuser, Markus Udo
Purpose: Laser-fenestrated thoracic endovascular aortic repair (LfTEVAR) in the aortic arch with covering of the left subclavian artery (LSA) orifice is challenging. To optimize fenestration, the so-called squid-capture technique has been introduced. We present here a modification to the technique that may help improve time-efficiency and safety. Technique: During the originally proposed squid-capture maneuver, the stent-graft is deployed in a preset snare wire loop, which is used to pull the stent graft toward the penetration device during in-situ fenestration. In preparation, the guidewire needs to be passed through the loop inside the aortic arch, which can be difficult and may predispose for embolic events. We propose here the creation of a "guidewire-through-snare-loop" configuration outside the body, which can then be reliably transferred into the aortic arch. The modified technique was successfully applied in a patient undergoing LfTEVAR for penetrating aortic ulcers. Conclusion: The proposed modification may help facilitate the squid-capture technique for LfTEVAR while saving time and resources. Given that LfTEVAR is becoming more frequently used, it is important to ensure technical success and safety of the procedure.